Multifactor Model of Risk and Return: APT to Fama and French Five Factor Model - Harold Kevin Alfredo (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This article is a literature review that discusses the articles of financial experts who popularized the method of calculating expected portfolio returns using economic factors that are considered to have an influence on the value of the portfolio greater than or equal to the influence exerted by market indices. The calculation method described in this study is an extension of the CAPM model introduced by Sharpe, Treynor, and Lintner in the 1960s. This article discusses starting from the method of Arbitrage Pricing Theory introduced by Ross in 1976, and the economic factors that become variables in the calculation of Arbitrage Pricing Theory proposed by NF. Chen, Roll, and Ross in 1986. then explained the calculation model Fama and French 3 Factor Model introduced in 1992, then Carhart 4 Factor Model which is an expansion of FF3FM, Pator-Stambaugh Model introduced by Lubos Pastor and Robert F. Stambaugh in 2001, and finally discusses the calculation model Fama and French Five Factor Model introduced in 2014 which is an expansion of FF3FM